IN MULTIMEDIA APPLICATIONS WITH VISUAL BASIC 5.0 OBJECT LINKING EMBEDDING INTERNATIONAL TEACHER AS A TEACHING TOOL - Muhammad Syakur; Sahni D. Purba. Skom. MM Sahni D. Purba. Skom. MM (Jurnal Sistem Informasi, 2002)
Since the days of yore, we know that television can replace the radio, the same is trueof the DOS-based programming language, the program can not utilize the capabilitiesof applications that already exist in one program. Programming languages aregenerally Windows-based languages on object-oriented programming, among others,MS Visual Basic, MS Visual C + + and Turbo others.Visual Basic is the operating system operating systems that have the ability OLE(Object Linking and Embedding), which is a collaboration between visualapplications. Where to create simple multimedia applications by utilizing thesupporting programs such as Active Movie. But for the show. AVI is not usingActive Movie directly.